Vowel Length Variation in the Pronunciation of Iraqi EFL Learners - Abdely, Ammar Abdul Wahab Abed Al (Elsya : Journal of English Language Studies, 2023)
This study examined the realization of English vowel length by EFL Iraqi learners. The study was basically interested in identifying whether Iraqi EFL learners are able to realize variations in vowel length based on following sounds. To this end, 20 male and female participants with 20-37 years age range participated in a production test. Before, they did so, they were asked to respond to a demographic questionnaire that aimed to ensure that all informants selected are suitable for the study aims and they well represent the population of the study. The production test included 60 English real words that provided English pure vowels (monophthongs) in different settings. The production was done using high quality smart phones. The recordings were analyzed using PRAAT to measure vowel length. The results showed that though variations in vowel length do exist where these vowels are located in different settings, paired samples T.Tests revealed that these variations were not statistically significant. Moreover, numerical differences in vowel length based on gender variable were present in all vowels; however, results of independent samples T.Tests indicated significant differences in closed settings only. No significant differences among vowel length means in the open setting were identified. EFL learners need to be exposed to native speech and pay attention to phonetic details so as to improve their pronunciation in general and vowel length realization in particular.